Characterisation of transient out-of-plane distortion of nipple welding with header component. (August 2015) - Vetri Selvan, R.; Sathiya, P.; Ravichandran, G.
Highlights: The thermal cycle and transient displacement in a nipple to header welding is analysed. The header to nipple multi-pass welding cause out-of-plane distortion of nipples. The effect of arc direction and start/stop points on out-of-plane distortion reported. Abstract: Welding distortions are experienced during the manufacture of boiler components using welding processes. Header is one of the significant boiler components currently fabricated using shielded metal arc welding (SMAW) process. Header is fabricated by welding tubes called nipple with thick-walled pipe called header using SMAW multipass circumferential fillet welding with T-joint orientation. The transient out-of-plane distortion of nipple experienced during welding with header is investigated in this paper. The analysis is carried out using the transient displacement and thermal cycle data obtained for two weld sequences. The thermal cycle and transient displacement data obtained during the investigation is having correlation with each other. The transient analysis reveals the influence of weld start/stop points. The out-of-plane distortion in X and Y directions is quantified. The distortion in X direction is influenced by weld start/stop points. The distortion in Y direction is influenced by welding direction. The influence of weld start/stop points over welding direction on distortion is quantified from the analysis. The transient analysis details are presented.